MANAJEMEN PENGAWAKAN PELAUT KAPAL NIAGA DAN TANGGUNG JAWAB PERUSAHAAN KEAGENAN AWAK KAPAL - Ade Chandra Kusuma (Sekolah Tinggi Maritim Yogyakarta, 2018)
In order to ensure the safety of the vessel to support the smoothness of sea vessel traffic it is necessary to have a crew of skill, skill and skill, therefore every ship that will sail shall be manned with adequate and capable crew to perform its duties on board according to the position of consideration ship tonnage, ship's machinery arrangement and shipping area. To become a crew member, it is necessary to have a requirement and to know what to fulfill in order to work on the vessel.